KAJI TERAP SISTEM INFORMASI REAL TIME PARAMETER AIR BAKU AMDK (AIR MINUM DALAM KEMASAN) BERBASIS TEKNOLOGI LORA GATEWAY - Imansyah, Fitri (Universitas Mataram, 2024)
Water contains physical, biological and chemical parameters. To determine water parameters, a sensor is needed which functions to convert physical, biological and chemical quantities into electrical quantities. This therapeutic study only tests the physical quantities contained in the water, such as pH levels, TDS, temperature and turbidity. Laboratory tests on water parameters using sensors are intended to obtain sensor characteristics and calibrate the sensors used with the aim that when the sensors are applied in the real environment, the conversion of physical quantities to electricity produced by the sensors will be close to the actual values. The amount of electricity produced by the sensor can be further managed for various purposes. Along with advances in technology in the field of telecommunications and information, water parameter data can be transmitted over long distances using transmitting devices to receiving devices. After the data reaches the recipient's device, the data can be displayed directly or forwarded to other devices using the internet network. The implementation of the long distance communication technology developed was tested at one of the companies/institutions in the field of bottled drinking water (AMDK) production, namely PT. Meteor Perkasa with the product brand